Effects of cyclic loading on screw loosening, vertical misfit, and microleakage at the fixture-angulated abutment interface - N Naseri; A Babasafari; E Jalalian; A Mazaheri; A Zarbakhsh (Islamic Azad University, 2021)
Background and Aim: This study assessed the effects of cyclic loading on screw loosening, vertical misfit, and microleakage at the fixture-angulated abutment interface. Materials and Methods: This in vitro study evaluated 12 implants in two groups (n=6). The implants were mounted in self-cure acrylic resin. The abutment screw was torqued to 30 N/cm by a digital torque-meter and re-torqued after 5 min. Six points at the fixture-abutment interface were inspected under a stereomicroscope (x75 magnification), and the distance between the two reference points was measured. Six implant-abutment assemblies then underwent cyclic loading (75 N, 1 Hz, 500,000 cycles) while the remaining six (control group) were stored at room temperature. The distance was measured again at the same 6 points after cyclic loading. Vertical misfit was calculated by subtracting the before and after values. The torque loss was measured by a digital torque-meter. The assemblies were then immersed in fuchsine and incubated at 37°C for 24 h. Next, the abutment was unscrewed and the fixtures were cut in half. The penetration depth of fuchsine was measured at 3 points of each fixture half under a stereomicroscope at x75 magnification, and the mean of the six measurements (entire fixture) was reported as the microleakage score of each sample. Data were analyzed using t-test. Results: Cyclic loading significantly increased the misfit (P=0.001) and microleakage (P=0.01), and decreased the detorque value (P=0.04). No case of screw loosening was noted in any group. Conclusion: Cyclic loading significantly increases the vertical misfit, microleakage, and torque loss.